Piggyback search for fast radio bursts using Nanshan 26 m and Kunming 40 m radio telescopes – I. Observing and data analysis systems, discovery of a mysterious peryton. Issue 3 (12th July 2019) - Men, Y P; Luo, R; Chen, M Z; Hao, L F; Lee, K J; Li, J; Li, Z X; Liu, Z Y; Pei, X; Wen, Z G; Wu, J J; Xu, Y H; et al.
ABSTRACT: We present our piggyback search for fast radio bursts using the Nanshan 26 m Radio Telescope and the Kunming 40 m Radio Telescope. The observations are performed in the L band from 1380 to 1700 MHz at Nanshan and the S band from 2170 to 2310 MHz at Kunming. We built the roach2 -based FFT spectrometer and developed the real-time transient search software. We introduce a new radio interference mitigation technique named zero-DM matched filter and give the formula of the signal-to-noise ratio loss in the transient search. Though we have no positive detection of bursts in about 1600 and 2400 h data at Nanshan and Kunming, respectively, an intriguing peryton was detected at Nanshan, from which hundreds of bursts were recorded. Perytons are terrestrial radio signals that mimic celestial fast radio bursts. They were first reported at Parkes and identified as microwave oven interferences later. The bursts detected at Nanshan show similar frequency swept emission and have double-peaked profiles. They appeared in different sky regions in about tens of minutes observations and the dispersion measure index is not exactly 2, which indicates the terrestrial origin. The peryton differs drastically from the known perytons detected at Parkes, because it appeared in a precise period of p  = 1.712 87 ± 0.000 04 s. Its origin remains unknown.